Smart electricity distribution networks, business models, and application for developing countries. (March 2018) - Jamasb, Tooraj; Thakur, Tripta; Bag, Baidyanath
Abstract: The electricity distribution industry in the developing world is dominated by public sector utilities. These utilities are technically and economically inefficient and face large financial losses that prevent further development of the networks. The reforms are introduced to unbundle the vertically integrated utilities and introduce private investment and management, but these efforts often fail due to poorly designed market and incentive models. Focusing on the electricity distribution in developing countries, we propose a business model based on organizing the utilities into distinct activities and businesses. In many developing countries political economy and weak investment conditions do not favour full privatization of utilities. However, in some activities 'competition for the market' and 'management contracts' can provide a partial role for the private actors. The model is based on the concepts of enterprise innovation, emphasizing external collaboration and partnerships and can be operationalized via specialization, where some specific tasks are outsourced. The proposed model can also be applied to developed countries as the energy sectors of both developing and developed countries are undergoing transformation due to new technologies such as communications, distributed generation (DGs), and active demand response. Highlights: Smart grids can contribute to development of the networks in developing countries. Implementation of smart grids is likely to require new business models. A business model is proposed based on business economics and enterprise innovation. The model offers partial participation in smart distribution networks.